The Practice of Markobar as a Medium for Internalizing Cultural Education in the Angkola Community - Sufrin Efendi Lubis; Riem Malini Pane; Abdul Sattar Daulay (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines markobar, an oral tradition of the Angkola community, as a medium for cultural education internalization. In the context of globalization, local cultural practices face increasing challenges that threaten their sustainability, particularly among younger generations. Although markobar persists in customary settings, its educational dimension remains underexplored in prior studies, which predominantly emphasize linguistic aspects. This research employs a qualitative ethnographic design conducted in Padangsidimpuan City and South Tapanuli Regency, North Sumatra. Data were collected through participant observation, in-depth interviews, and documentation, involving traditional leaders, practitioners, community members, and youth. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with validity ensured through triangulation and member checking. The findings demonstrate that markobar functions as a contextual and non-formal educational medium embedding five core values: respect, responsibility, togetherness, politeness, and ethical communication. The internalization process occurs through observation, participation, and habituation. However, its effectiveness is constrained by declining youth engagement, weakening mastery of customary language, and digital cultural influences. Theoretically, markobar aligns with social learning theory and experiential cultural education. Sociologically, it serves as a mechanism for value reproduction and social cohesion. Nonetheless, a gap persists between normative values and contemporary practices, reflecting ongoing negotiation between tradition and modernity.